Interventions performed by nurses to improve communication with the visually impaired - Débora Oliveira Favretto; Emília Campos de Carvalho; Silvia Rita Marin da Silva Canini (Rev Rene)
This study aimed to identify which interventions nurses apply to improve communication with visually impaired patients. Twenty-fi ve nurses received a form with 17 activities, to indicate whether they had performed each of them or not, besides the reasons for not performing them. More than half of the nurses had practiced 52.94% of the 17 activities. Other activities (47.06%) which were not very used included activities that help in the individual’s socialization; those that are not practiced due to a lack of knowledge/resource and activities that can be performed. Thus, these professionals need new knowledge in order to improve care delivery to visually impaired patients.